An experimental test of two policies to increase donations to public projects - López Pérez, Raúl (2020)
This paper uses lab-in-the-field experiments and theory to explore why people give money to gov-ernments. We assume that giving is motivated by outcome–oriented or consequentialist norms, andconditional on (a) others’ behavior and (b) beliefs about how competent the government is. The evidencefrom a lab experiment in Peru is in line with this. On the other hand, we analyze the potential effectsof two policies to increase giving, observing that less people give zero if they are informed about (i)two specific government projects (a subway line and a children’s hospital) or (ii) that some well-knownOlympic medalist pays punctually her taxes, according to public information released by the Peruviantax Agency. Our findings contribute to a burgeoning literature on tax morale and are arguably relevantto understand taxpayers’ non-selfish reasons to pay (or evade) their taxes.